Design And Build A Website-Based Accounting Information System With Extreme Programming Methods - Alamsyah, Noor; Murpratiwi, Santi Ika; Albar, Moh Ali; Jatmiko, Andy Hidayat; Huwae, Raphael Bianco; Trieanto, Agil (Information Technology and Science (ITScience), 2024)
The need to use information systems in the digital world is absolutely necessary for a company. With an information system, it will be easier for companies to process data, store data and make decisions. One of the information system implementations that companies need is an accounting information system that regulates cash receipts and disbursements. However, currently there are still many companies that still store their transaction data traditionally using Microsoft Excel and are not yet computerized. Based on data obtained from interviews conducted with a company accountant, it is known that errors occurred when processing data which had an impact on financial reports, namely when inputting data into Microsoft Excel there was still data that was missed, resulting in incorrect financial reports. balance due to errors in recording transactions. By implementing a website-based cash accounting information system, it makes it easier for accountants to collect data in the cash book. This information system was created using the PHP programming language with Laravel as the framework and Extreme Programming as the development method. Extreme Programming was chosen because it requires good and regular communication with the client to adjust system needs. This information system consists of 3 iterations which have a processing time of 32 days. System testing was carried out using User Acceptance Testing with an average percentage obtained of 86.8%. These results can be indicated that the system is running properly and can be understood well by the client or user.